The physicochemical properties, proximate composition and antioxidant property of purees and ready-to-drink juices of bignay [Antidesma bunius (Linn) Spring], calamansi [xcitrofortunella microcarpa (Bunge) wijnands], dalandan [citrus sinensis (Linn) osbeck], and passion fruit (passiflora edulis sims forma flavicarpa) - Bravo, Erwin Caesar V.; Santiago, Dennis Marvin O. (2011)
The physicochemical properties, proximate composition, vitamin C content and antioxidant activity of bignay, calamansi, dalandan and passionfruit purees and their ready-to-drink (RT juices were analyzed and compared. Processing of fruit purees into their RTD juices decrease the pH for bignay and dalandan and increase for calamansi and passionfruit. The total titratable acid content generally decreased since the purees were diluted processing. The total soluble solids increased except in passion fruit. The moisture content, crude protein, and ash content generally decreased while the total sugar content increased. Vitamin C was highest in bignay puree and its RTD juice. It was detected in the other fruit purees but was lost after processing. There were no significant diferences in the site-specific activities of the fruit purees, the RTD fruit juices and between the fruit purees and their RTD juices. The same was true for the non-site-specific scavenging activities of the fruit purees and RTD juices.
Keywords: Fruit composition; Fruit -- Nutrition; Fruit juices -- Health aspects; Fruit juices -- Nutrition; Bignay (fruit); Citrus fruits; Passion fruit juice